Carbon nanotubes exhibit fibrillar pharmacology in primates. - Simone Alidori; Daniel L J Thorek; Bradley J Beattie; David Ulmert; Bryan Aristega Almeida; Sebastien Monette; David A Scheinberg; Michael R McDevitt (PLoS ONE, 2017)
Nanomedicine rests at the nexus of medicine, bioengineering, and biology with great potential for improving health through innovation and development of new drugs and devices. Carbon nanotubes are an example of a fibrillar nanomaterial poised to translate into medical practice. The leading candidate material in this class is ammonium-functionalized carbon nanotubes (fCNT) that exhibits unexpected pharmacological behavior in vivo with important biotechnology applications. Here, we provide a multi-organ evaluation of the distribution, uptake and processing of fCNT in nonhuman primates using quantitative whole body positron emission tomography (PET), compartmental modeling of pharmacokinetic data, serum biomarkers and ex vivo pathology investigation. Kidney and liver are the two major organ systems that accumulate and excrete [86Y]fCNT in nonhuman primates and accumulation is cell specific as described by compartmental modeling analyses of the quantitative PET data. A serial two-compartment model explains renal processing of tracer-labeled fCNT; hepatic data fits a parallel two-compartment model. These modeling data also reveal significant elimination of the injected activity (>99.8%) from the primate within 3 days (t1/2 = 11.9 hours). These favorable results in nonhuman primates provide important insight to the fate of fCNT in vivo and pave the way to further engineering design considerations for sophisticated nanomedicines to aid late stage development and clinical use in man.